The Challenge of Nuclear-Armed Regional Adversaries - Ochmanek, David (RAND Corporation, 2008)
Deterrence of nuclear use through the threat of retaliation could be highly problematic in many plausible conflict scenarios with nuclear-armed regional adversaries. This could compel U.S. leaders to temper their military and political objectives if they come into conflict with these states. This book examines the reasons behind this important shift in the international security environment and its strategic and force planning implications.